Indigenous weather knowledge - Australia. Bureau of Meteorology (Canberra : Commonwealth Bureau of Meteorology, 2004)
Website for the new Bureau of Meteorology Indigenous Weather Knowledge website, which is the result of a joint effort involving the Indigenous communities, Aboriginal and Torres Strait Islander Commission (ATSIC), the Bureau of Meteorology, Monash University's Centre for Australian Indigenous Studies (CAIS) and School of Geography and Environmental Science; still in its developmental stages, the site includes a brief history of Indigenous traditional ecological knowledge, which consists largely of an intimate knowledge of plant and animal cycles and the details of the intricate connections between these, which have been observed over thousands of years by Aboriginal people and passed down from generation to generation; website also provides Indigenous seasonal descriptions, and calendars for several areas in Australia detailing information about climate, safety of travel, food and culture.
Indigenous climate; Weather & culture; About the IWK; Bureau of Meteorology; Climate zones; Feedback; Seasonal calendars.
Title from website (viewed on 17/7/09)
Text and graphics.
Selected for archiving
Keywords: Meteorology -- Australia; Traditional ecological knowledge -- Australia; Dharawal / Tharawal / Dariwal people (S59) (NSW SI56-09); Environment - Climate and weather - Seasons; Indigenous knowledge - World view - Ethnotaxonomy; Jardwadjali language (S27) (Vic SJ54-03); Jardwadjali people (S27) (Vic SJ54-03); Jawoyn people (N57) (NT SD53-09); Miriwoong / Miriuwung people (K29) (WA SD52-14); Wardaman language (N35) (NT SD52-16); Wardaman people (N35) (NT SD52-16); Yanyuwa / Yanuwa people (N153) (NT SE53-04); Australia; Gariwerd / Grampians (W Vic SJ54-03, SJ54-07, SJ54-08); Katherine (NT Top End SD53-09); Walabunnba